Implementasi Yuridis Dan Psikososial Anak Sebagai Korban Perceraian Akibat Kekerasan Dalam Rumah Tangga - Kristin Nadya Anggela Siahaan; Asep Suherman (CV. ITTC INDONESIA, 2024)
Abstract Domestic child abuse is still often found among the community. Children who should get good behavior from parents often become an outlet for the emotions of those around them. Families who should provide a sense of security and comfort, instead instill a sense of trauma in the child's life. Domestic violence is any act of violence committed by a husband or wife against their spouse or child which results in physical, psychological, economic and sexual problems. The facts show that domestic violence has a significant negative impact on children as victims. In addition, domestic violence is also the cause of many divorce cases in Indonesia. Most children are taught to be obedient and obey their parents through violence. This research reveals that physical and psychological violence against children by parents is still common, negatively affecting their growth. It is necessary to protect the rights of children victims of violence, especially the rights to physical, mental, social growth and development. This research uses a literature study approach method because it collects data from books, journals, the internet, or other written literature as a basis for writing. This research aims to explain the impact experienced by children who are victims of domestic violence.